Trends in stroke incidence among elderly low-income residents of rural China: a population-based study from 1992 to 2016 - Lu, Hongyan (Aging (Albany NY), 2018)
In China, >70% of stroke deaths occur in people aged ≥65 years. However, trends in the stroke incidence among elderly people are unclear. We aimed to determine trends in the stroke incidence among elderly people in rural China. This was a population-based surveillance study conducted in Tianjin, China. Stroke events and all deaths were registered annually. Trends and annual proportion of change in incidence of first-ever stroke were evaluated from 1992 to 2016. The age-standardized incidence of first-ever stroke increased annually by 3.7% overall in elderly people (2.7% for men; 5.0% for women; all P<0.05). However, from 2008 to 2016, there was no significant change in the trends of stroke incidence among elderly people, across gender and subtypes. The proportion of elderly patients with first-ever stroke decreased by 1.1% annually. In contrast to young patients, annual changes in the incidence of stroke tended to be slight in elderly patients (3.7% vs. 9.5%) with greater increase in female patients than those in male patients (2.7% vs. 10.3% for men; 5.0% vs. 8.9% for women). Thus, the control of risk factors for stroke among elderly people is crucial, especially among older women, to reduce the burden of stroke in China.